(untitled) (Jurnal Bakti Masyarakat Indonesia, 2025)
Accounting lessons are often considered boring and difficult. The closeness of accounting to arithmetic and mathematics often creates antipathy among students before starting to study accounting. Meanwhile, accounting lessons are one of the mandatory elective lessons that are characteristic of the internal Merdeka Belajar curriculum at SMA Kristen Yusuf. Therefore, accounting teaching techniques must be more varied so that students can easily grasp the lessons. When the Untar PKM team presents accounting material in the form of cash flow reporting, the team looks for appropriate learning techniques for students to more easily understand how to make cash flow reports. The cash flow report consists of 3 (three) parts, namely cash flow from operating activities, cash flow from investment activities and cash flow from financing activities. A learning technique that is quite interesting and easy so that students are able to understand this material is the jigsaw cooperative learning technique. Students will be divided into 3 (three) groups according to the cash flow section in the cash flow report. Students will be given time to understand and solve cases in the form of cash flow analysis for each activity. After the three groups have completed their respective parts of the case, they will be combined to see the cash flow report as a whole and understand thoroughly how cash flow moves within a company. Students were enthusiastic during this training and found it easier to understand cash flow reports. ABSTRAK Pelajaran akuntansi seringkali menjadi pelajaran yang dianggap membosankan dan sulit. Kedekatan akuntansi dengan berhitung dan matematika seringkali membuat pelajar antipati terlebih dahulu sebelum memulai pembelajaran akuntansi. Sedangkan pelajaran akuntansi merupakan salah satu pelajaran pilihan wajib yang menjadi ciri khas internal kurikulum merdeka belajar di SMA Kristen Yusuf. Oleh karena itu teknik pengajaran akuntansi harus lebih variatif agar siswa mudah menangkap pelajaran. Kegiatan PKM kali ini di SMA Kristen Yusuf akan mengembangkan teknik jigsaw untuk pelatihan akuntansi. Ketika tim PKM Untar akan membawakan materi akuntansi berupa laporan arus kas, maka tim mencari teknik pembelajaran yang tepat bagi siswa untuk lebih mudah memahami cara membuat laporan arus kas. Laporan arus kas terdiri dari 3 (tiga) bagian, yaitu arus kas kegiatan operasi, arus kas kegiatan investasi dan arus kas kegiatan pembiayaan. Teknik pembelajaran yang cukup menarik dan mudah agar siswa mampu memahami materi ini adalah teknik pembelajaran kooperatif teknik jigsaw. Siswa akan dibagi menjadi 3 (tiga) kelompok sesuai dengan bagian arus kas dalam laporan arus kas. Siswa akan diberikan waktu untuk memahami dan memecahkan kasus yang berupa analisa arus kas untuk tiap aktivitas. Setelah ketiga kelompok menyelesaikan bagian dari kasus masing masing, akan digabungkan untuk melihat laporan arus kas secara utuh dan memahami secara menyeluruh bagaimana arus kas bergerak dalam suatu perusahaan. Siswa antusias saat pelaksanaan pelatihan ini dan merasa lebih mudah memahami laporan arus kas